Improving Wireless Communication OFDM systems based on image processing - Jaber, Ali (The Indonesian Journal of Computer Science, 2025)
One of the most common methods used in modern communication systems is orthogonal frequency division multiplexing (OFDM) to reduce the resistance to selective frequency fading. Another important reason is the possibility of reducing interference between symbols. However, there are also drawbacks, including the high peak-to-average power ratio (PAPR), which affects the power loss, increasing the complexity of transmitters. In the proposed study, we reduce PAPR in OFDM-based systems by hiding information in the image to maintain data security. In this steganography method, we insert digital text into the image and hide it, thus providing greater reliability while simultaneously reducing the PAPR required in OFDM. Text steganography is a method for hiding a large amount of information, which is helpful in OFDM. This also helps keep the system free from noise. Therefore, sending hidden data over communication channels is a good way to avoid interference, as image transmission is less affected by interference, and upon receipt, the main structure can be reconstructed to extract the hidden data and the original image. This is a way to preserve communication channels, which is the main objective of this study. The proposed method was evaluated by comparing the results with other methods, and it was found that the amount of data loss is reduced to 50% compared to the conventional method, which is the most important part. Also, the transmitted signal power has improved PAPR to 5.9 dB compared to the conventional method, which helps improve the quality of wireless transmission of the OFDM signal